Estudio de propiedades mecánicas de un material compuesto de matriz en polipropileno con fibra de guadua y polvo de cerámica. (2020)
The use of naturally occurring fibers as a reinforcement in Composite Materials (CM) has been taking hold in recent years. In this case, it is a recycled CM with polypropylene matrix (PP) from lids of different packaging of everyday consumer products; for reinforcement, it was chosen to use natural Guadua Angustifolia fiber and tenacious ceramic powder. The Guadua fiber was obtained under drying conditions and immunized according to the process of the company that distributes it, to reduce its moisture and to prevent the appearance of fungi and lichens, allowing a correct adhesion with the matrix. Tenacious ceramic powder is also a recycled material, it was obtained from ceramic floors that were crushed and sprayed before insertion into the CM. The proportions used to manufacture the MC specimens were: one with 100% PP and others with different composition of the MC, where the PP matrix remained with 60%, and the reinforcement materials were combined in the following proportions, obtaining three samples as well: one with 30% fiber and 10% ceramic, another with 33% fiber and 7% ceramic and one last with 35% fiber and 5% ceramic. Once the CM specimens were obtained, mechanical, voltage tests according to ASTM 638D for polymers were performed and bending with ASTM 790D for reinforced plastics. The results obtained were analyzed, finding that the PP stress elasticity module increased by 53.49 % by adding guadua by 35% and ceramic by 5%; in such a way that, it is allowed to continue more studies of the CM with different percentages, modifying the alignment of the fiber and by using the other types of guadua that can be found in the country.